Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1152/ajpgi.1989.257.4.g616
|View full text |Cite
|
Sign up to set email alerts
|

New insights into lactase and glycosylceramidase activities of rat lactase-phlorizin hydrolase

Abstract: Lactase-phlorizin hydrolase, a small intestinal disaccharidase, has been considered mainly an enzyme important only for the hydrolysis of lactose. After weaning in most mammals lactase-specific activity falls markedly, and, functionally, adult mammals are considered to be lactase deficient. However, the persistence of low levels of lactase activity in adulthood has never been explained. In addition, it has been suggested that lactase-phlorizin hydrolase is associated with glycosylceramidase activity when the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 0 publications
0
26
0
3
Order By: Relevance
“…Alkaline sphingomyelinase is present in the intestinal mucosa (25)(26)(27), and the glycosylceramidase activity in the intestine is due to lactase-phlorizin hydrolase (28,29). Neutral ceramidase encoded by Asah2 is also present in the small intestine (30).…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline sphingomyelinase is present in the intestinal mucosa (25)(26)(27), and the glycosylceramidase activity in the intestine is due to lactase-phlorizin hydrolase (28,29). Neutral ceramidase encoded by Asah2 is also present in the small intestine (30).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated that alkaline sphingomyelinase is present in the intestinal mucosa (35)(36)(37) and that the glycosylceramidase activity in the intestine is due to lactase-phlorizin hydrolase ( 38,39 ). Neutral ceramidase encoded by Asah2 is also present in the small intestine ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier investigations have also suggested that lactase-phlorizin hydrolase, a small intestinal disaccharidase, exhibits glycosylceramidase activity in the intestine and plays an important role in the digestion of dietary glycolipids [123,124]. In addition, other studies have provided evidence on the existence of ceramidase in intestinal content [125,126].…”
Section: Digestion Absorption and Uptake By Keratinocytes Of Oral Pmentioning
confidence: 99%